Cinema of discontent : representations of Japan's high-speed growth - Sasaki, Tomoyuki (SUNY series, horizons of cinema., 2022)
Uses popular films to reveal the tensions generated during Japan's postwar ""economic miracle,"" challenging the prevailing view that it was a story of great national success.